A prospective evaluation of plasma phospholipid fatty acids and breast cancer risk in the EPIC study - Chajès, V; Assi, N; Biessy, C; Ferrari, P; Rinaldi, S; Slimani, N; Lenoir, G; Baglietto, L; His, M; Boutron-Ruault, M; Trichopoulou, A; Lagiou, P; et al. (Oxford University Press, 2017)
Background: Intakes of specific fatty acids have been postulated to impact breast cancer risk but epidemiological data based on dietary questionnaires remain conflicting. Material and methods: We assessed the association between plasma phospholipid fatty acids and breast cancer risk in a case-control study nested within the European Prospective Investigation into Cancer and Nutrition (EPIC) study. Sixty fatty acids were measured by gas chromatography in pre-diagnostic plasma phospholipids from 2,982 incident breast cancer cases matched to 2,982 controls. Conditional logistic regression models were used to estimate relative risk of breast cancer by fatty acid level. The false discovery rate (q-values) was computed to control for multiple comparisons. Subgroup analyses were performed by estrogen receptor (ER) and progesterone receptor (PR) expression in the tumours. Results: A high level of palmitoleic acid (odds ratio, OR for the highest quartile compared with the lowest OR[Q4-Q1=1.37; 95%CI=1.14-1.64; p for trend=0.0001, q-value=0.004) as well as a high desaturation index (DI16) (16:1n-7/16:0) (OR[Q4-Q1=1.28; 95%CI=1.07-1.54; p for trend=0.002, q-value=0.037), as biomarkers of de novo lipogenesis, were significantly associated with increased risk of breast cancer. Levels of industrial trans-fatty acids were positively associated with ER-negative tumors (OR for the highest tertile compared with the lowest [T3-T1]=2.01; 95% CI=1.03-3.90; p for trend=0.047), while no association was found for ER-positive tumors (P-heterogeneity =0.01). No significant association was found between n-3 polyunsaturated fatty acids and breast cancer risk, overall or by hormonal receptor. Conclusion: These findings suggest that increased de novo lipogenesis, acting through increased synthesis of palmitoleic acid, could be a relevant metabolic pathway for breast tumorigenesis. Dietary trans fatty acids derived from industrial processes may specifically increase ER-negative breast cancer risk.